Looking beyond the incumbent: The effects of exposing corruption on electoral outcomes - Alberto Chong; Ana L. De La O; Dean Karlan; Leonard Wantchekon (Yale University, Economic Growth Center, 2012)
Does information about rampant political corruption increase electoral participation and the support for challenger parties? Democratic theory assumes that offering more information to voters will enhance electoral accountability. However, if there is consistent evidence suggesting that voters punish corrupt incumbents, it is unclear whether this translates into increased support for challengers and higher political participation. We provide experimental evidence that information about copious corruption not only decreases incumbent support in local elections in Mexico, but also decreases voter turnout, challengers' votes, and erodes voters' identification with the party of the corrupt incumbent. Our results suggest that while flows of information are necessary, they may be insufficient to improve political accountability, since voters may respond to information by withdrawing from the political process. We conclude with a discussion of the institutional contexts that could allow increased access to information to promote government accountability.
Keywords: D72; D73; D82; D83; 330; Corruption; Accountability; Elections; Voting; Information; Korruption; Gesellschaftliches Bewusstsein; Politisches Ziel; Wahlverhalten; Wahlbeteiligung; Mexiko